Structures, plasmon-enhanced luminescence, and applications of heterostructure phosphors. Issue 37 (21st September 2021) - Wang, Xiangfu; She, Min; Gu, Wenqin; Bu, Yanyan; Yan, Xiaohong
Abstract : The structures, plasmon-enhanced luminescence and mechanism of metal/fluorophore heterostructure composites, such as core–shell nanocrystals, multilayers, adhesion, islands, arrays, and composite optical glass, are reviewed in detail. Abstract : Heterostructure phosphor composites have been used widely in the fields of targeted bio-probes and bio-imaging, hyperthermia treatment, photocatalysis, solar cells, and fingerprint identification. The structures, plasmon-enhanced luminescence and mechanism of metal/fluorophore heterostructure composites, such as core–shell nanocrystals, multilayers, adhesion, islands, arrays, and composite optical glass, are reviewed in detail. Their extended applications were explored widely since the surface plasmon resonance effect increased the up-conversion efficiency of fluorophores significantly. We summarize their synthesis methods, size and shape control, absorption and excitation spectra, plasmon-enhanced up-conversion luminescence, and specific applications. The most important results acquired in each case are summarized, and the main challenges that need to be overcome are discussed.